Utilizing Microsoft Teams to Enhance Students’ Competence in Writing Recount Text - Cholila Achmad Juri; Kartin Lihawa; Rahman Taufiq Dako (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2023)
Students’ writing competence is one of language skills that should be improved. This study aimed at describing the utilization of Microsoft Teams and finding out whether it can enhances the students’ competence in writing historical recount text. The design of action research used the modification of Kemmis and McTaggart’s model. The research finding showed that the total of the successful students in learning for the first cycle was 41,94%, while for the second cycle was 87.1%. It means that the utilization of Microsoft Teams can enhance the students’ competence in writing historical recount text.